2016
DOI: 10.1007/s11325-016-1374-4
|View full text |Cite
|
Sign up to set email alerts
|

Obstructive sleep apnea is independently associated with subclinical coronary atherosclerosis among middle-aged women

Abstract: Moderate to severe OSA is independently associated with the presence of CAC in middle-aged women. These results reinforce the concept that women are also susceptible to the cardiovascular consequences of OSA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
18
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 36 publications
2
18
0
1
Order By: Relevance
“…We found only a trend for higher CAC values in OSA. Although previous studies showed a significant associa- Lutsey et al, 2015;Luyster et al, 2014;Matthews et al, 2011;Medeiros et al, 2017;Seo et al, 2017;Sorajja et al, 2008;Weinreich et al, 2013), this relationship became insignificant after adjusting for BMI (Kim et al, 2010;Luyster et al, 2014;Matthews et al, 2011;Seo et al, 2017) or comorbidities (Seo et al, 2017). In addition, the independent relationship between high CAC and OSA was present only in moderate to severe (Medeiros et al, 2017) and…”
Section: Discussionmentioning
confidence: 86%
See 4 more Smart Citations
“…We found only a trend for higher CAC values in OSA. Although previous studies showed a significant associa- Lutsey et al, 2015;Luyster et al, 2014;Matthews et al, 2011;Medeiros et al, 2017;Seo et al, 2017;Sorajja et al, 2008;Weinreich et al, 2013), this relationship became insignificant after adjusting for BMI (Kim et al, 2010;Luyster et al, 2014;Matthews et al, 2011;Seo et al, 2017) or comorbidities (Seo et al, 2017). In addition, the independent relationship between high CAC and OSA was present only in moderate to severe (Medeiros et al, 2017) and…”
Section: Discussionmentioning
confidence: 86%
“…Differences in diagnostic methods may lead to underdiagnosis or underestimation of severity in some patients. Moreover, studies also varied in diagnostic criteria for OSA, ranging from AHI score of 5/hr (Matthews et al., ; Medeiros et al., ; Nakanishi‐Minami et al., ; Sorajja et al., ; Weinreich et al., ) to 10/hr (Sharma et al., ), in addition to the combination of objective measures and symptoms (Pusuroglu et al., ). We hypothesised that even mild OSA may be associated with CAD (Hu et al., ); therefore, we chose AHI score of 5/hr as a diagnostic threshold without taking into account symptoms or comorbidities.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations